Distribution co-opetition and multi-level inventory management performance: An industry analysis and simulation. Issue 1 (March 2015) - Shockley, Jeff; Fetter, Gary
Abstract Research notes supply chains where competitors selling the same types of products at the same level of the supply chain may work together to achieve superior profits, using the term "co-opetition" to describe the phenomenon. Using a co-opetitive supply chain design in the bearing and power transmission industry as a practical guide, we develop a multi-level simulation to compare the effects of serial versus a co-opetitive supply chain design on inventory management, order fulfillment, and cost performance. Specifically, we examine supply chain network membership, product demand volatility, and in-transit shipping consolidation effects in our model. This research aims to (1) quantify the performance benefits to be expected from co-opetition and (2) examine the structural conditions present that may enable these co-opetitive networks to achieve value-added inventory cost and delivery performance. We find that the co-opetitive distribution strategies can significantly improve inventory management performance when supply chains have a larger number of competing products, manufacturer׳s product freight-billing allows for in-transit shipping, and supply networks have a longer reach.